Survival trends in oral cavity cancer patients treated with surgery and adjuvant radiotherapy in a tertiary center of Northern India: Where do we stand compared to the developed world? - Nishant Lohia; Sharad Bhatnagar; Sankalp Singh; Manoj Prashar; Anand Subramananiam; Sundaram Viswanath; P K Sahu; Ajay Rai (Wolters Kluwer Medknow Publications, 2019)
Introduction: Oral cavity cancer is the third most common cancer in India. It presents a major burden on health services in India due to the widespread and rampant use of tobacco. Moreover, as per the Indian Council of Medical Research 2016 data, it ranks the fifth in overall mortality rate among different cancers prevalent in India. Aims and Objectives: The aim was to study and present our data on patient- and tumor-related factors as well as overall survival (OS) among patients of oral cavity cancer treated with surgery and radiotherapy at our center. The objective was to find the difference in OS in various subgroups of patients at 2 and 5 years from treatment. Materials and Methods: This was a retrospective study carried out in a tertiary care center of North India. The data collected were of patients treated between November 12 and November 16. A total of 112 cases of oral cavity cancers were studied. The patient-related variables that were analyzed included age, gender, history of tobacco or alcohol use, and presence of preexisting comorbidities. The tumor-related factors that were studied were tumor subsite, stage, and histological grade. OS of patients with varying parameters was compared at 2 and 5 years. Results: OS at 5 years for Stage I was 100% and decreased to 85% for Stage II. For Stages III and IV, the 5-year survival was a mere 43% and 42%, respectively. Conclusion: Treatment results at our center were comparable to world literature.